A Need Analysis for Learning English to Young Learners - Firda Amalia; Albiansyah Albiansyah (TLEMC (Teaching and Learning English in Multicultural Contexts), 2023)
A growing body of literature has discussed need analysis in a certain domain. The issue raised since English to Young Learners was important to support the process of language learning in the classroom. The present study was employed to investigate student's need analysis, especially for the teaching of English to young learners in the elementary school level. The data were collected through questionnaires, interviews, and analyzing the documents of sample students. Questionnaires were distributed to 25 students of grade 5A and 5B, and interviews were conducted with an English teacher of grade 5 at an elementary school in Jakarta. The findings revealed that the students were expected to master language skills so that they could be more confident in reading and writing. Furthermore, they also have several preferable topics to be discussed in the learning process such as family and friends, foods, or meals. They prefer to have topics that could be related to their daily life and their background knowledge. Moreover, there are several factors that may hinder the teaching of reading and writing. The irrelevant topics to their daily life and interest, lack of vocabulary knowledge, and anxiety in writing were the factors that made them hard to read and write. Therefore, the development of class materials needed to be relevant to students' needs.Â Keywords: Need Analysis, English to Young Learners, Learning Materials